Identification of a Novel Protein Arginine Methyltransferase 5 Inhibitor in Non-small Cell Lung Cancer by Structure-Based Virtual Screening - Wang, Qianqian; Xu, Jiahui; Li, Ying; Huang, Jumin; Jiang, Zebo; Wang, Yuwei; Liu, Liang; Leung, Elaine Lai Han; Yao, Xiaojun (Frontiers in Pharmacology, 2018)
Protein arginine methyltransferase 5 (PRMT5) is able to regulate gene transcription by catalyzing the symmetrical dimethylation of arginine residue of histone, which plays a key role in tumorigenesis. Many efforts have been taken in discovering small-molecular inhibitors against PRMT5, but very few were reported and most of them were SAM-competitive. EPZ015666 is a recently reported PRMT5 inhibitor with a new binding site, which is different from S-adenosylmethionine (SAM)-binding pocket. This new binding site provides a new clue for the design and discovery of potent and specific PRMT5 inhibitors. In this study, the structure-based virtual screening targeting this site was firstly performed to identify potential PRMT5 inhibitors. Then, the bioactivity of the candidate compound was studied. MTT results showed that compound T1551 decreased cell viability of A549 and H460 non-small cell lung cancer cell lines. By inhibiting the methyltransferase activity of PRMT5, T1551 reduced the global level of H4R3 symmetric dimethylation (H4R3me2s). T1551 also downregulated the expression of oncogene FGFR3 and eIF4E, and disturbed the activation of related PI3K/AKT/mTOR and ERK signaling in A549 cell. Finally, we investigated the conformational spaces and identified collective motions important for description of T1551/PRMT5 complex by using molecular dynamics simulation and normal mode analysis methods. This study provides a novel non-SAM-competitive hit compound for developing small molecules targeting PRMT5 in non-small cell lung cancer.